Experiences of health care providers managing sexual assault victims in the emergency unit Part 2: Discussion of results and literature control - Rebecca M. Skhosana; Mmapheko D. Peu (AOSIS, 2009)
The objective of this study was to explore and describe the experiences of health care providers managing sexual assault victims in the emergency unit of a community hospital in the Nkangala district in the Mpumalanga Province. A qualitative, phenomenological design was applied. Purposeful sampling was used to select participants from health care providers who were working in the emergency unit and had managed more than four sexual assault victims. Data were collected by means of individual interviews and analysed according to the Tesch method of data analysis by the researcher and the independent co-coder. Main categories, subcategories and themes were identified. Participants expressed their emotions, challenges and police attitudes and behaviours, as well as inconsistencies in guidelines and needs identification. It was recommended that members of the multidisciplinary team engage in community activities and that the community participate in matters pertaining to sexual assault. Government should develop clear guidelines that are applicable to rural and urban South Africa. Health care sciences should aim to train more forensic nurses. All relevant departments should work together to alleviate the complications caused by sexual assault incidents. Opsomming Die doel van hierdie studie was om die ervaringe van gesondheidsorgverskaffers wat slagoffers van seksuele aanranding in die ongevalle-eenheid van 'n gemeenskapshospitaal in die Nkangala-distrik in die provinsie van Mpumalanga hanteer, te ontgin en te beskryf. 'n Kwalitatiewe fenomenologiese ontwerp is toegepas. Doelbewuste steekproefneming is gebruik om deelnemers te selekteer uit die groep gesondheidsorgverskaffers wat in die ongevalle-eenheid werksaam was en meer as vier slagoffers van seksuele aanranding hanteer het. Data is by wyse van individuele onderhoude ingesamel en volgens die Tesch-metode van data-analise deur die navorser en die onafhanklike medekodeerder geanaliseer. Hoofkategorieë, subkategorieë en temas is geïdentifiseer. Deelnemers het uitdrukking gegee aan hulle emosies, uitdagings, die houding en gedrag van polisiebeamptes, teenstrydighede in riglyne en behoefte-identifikasie. Aanbevelings is dat multidissiplinêre spanlede betrokke moet wees by gemeenskapsaktiwiteite en dat die gemeenskap moet deelneem aan sake wat verband hou met seksuele aanranding. Die regering moet duidelike riglyne ontwikkel wat op landelike en stedelike Suid-Afrika van toepassing is. Gesondheidsorgwetenskappe moet daarop gerig wees om meer forensiese verpleegkundiges op te lei. Alle toepaslike departemente moet saamwerk om die komplikasies te verlig wat deur voorvalle van seksuele aanranding veroorsaak word.